Grammar Learning Strategies Practice: An Investigation of Strategies-Based Instruction Effect on Grammatical Competence - Ismail Ismail; Dedi Dedi (Hasanuddin University, 2021)
Grammar competence as an essential part in learning language has to be mastered by every language learner. Students, especially in higher education, need to possess the knowledge of grammar rules to produce academic products that maintain the grammatical aspects in every task. A new notion in learning grammar by employing grammar learning strategies becomes an alternative way for students in mastering grammar. Since many students are not aware of grammar learning strategies, the need to conduct strategies training in the classroom context is a solution. Empowered by styles and strategies-based instruction, this study aimed to determine the effect of grammar learning strategies on the grammatical competence of second semester students of Universitas Muslim Indonesia. Quasi-experimental design under quantitative research consisting of pre-test, eight meetings of treatment, and post-test was employed to compare the groups’ performance in grammar test. The data were obtained by using two kinds of research instruments: grammar test and questionnaire. In analyzing the data, this study employed the independent sample t-test and frequency of questionnaire. The result of statistical analysis showed that independent t-test which compared the students’ score on post-test revealed a value of p>0.05. It means that there was no significant difference between students taught with and without grammar learning strategies. The result yields some implications of having grammar learning strategies in classroom context. The students’ personal traits and experiences put some influences on the effect of strategies training. The duration of training also put contribution toward the students’ skills in employing the appropriate strategies in solving grammar problems.